Managing urban land use sprawl in developing countries using GIS and remote sensing : towards resilient cities - Hj. Mohd. Noor, Norzailawati; Abdullah, Alias; Mazlan, Hashim; Asmawi, M. Zainora (2012)
The rapidly expanding urban areas of the world constitute an environmental challenge for the 21st century that requires both new analytic approaches and new sources of data and information in micro and macro level. Management of land use sprawl in urban area especially in developing countries using GIS and Remote sensing tools still in vague although these tool may provide the benefit on fundamental observations of urban encroachment and environmental monitoring that are not available from other sources (Batty and Howes, 2001). Therefore, this paper attempts to analyze the capability and reviewing the research and works done recently on GIS and remote sensing in managing urban land use sprawl in developing countries in order to increase the resilience of cities with diverse dynamics.